2022
DOI: 10.1186/s13104-022-06217-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between glycated hemoglobin A1c levels and exacerbation status in the patients with chronic obstructive pulmonary disease

Abstract: Objective This study was performed in Razi Hospital, Rasht, Iran, between March 2016 and August 2018 on a population of chronic obstructive pulmonary disease (COPD) patients (56 as COPD exacerbation group and 56 as COPD stable group). Study variables include age, sex, occupation, body mass index (BMI), cigarette consumption, duration of COPD, annual hospitalization, dyspnea, glycated hemoglobin (HbA1c), FEV1, and FEV1/FVC indices. Result The mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous studies reported the association of HbA1c level with the exacerbation of COPD, which is a severe complication associated with increased short-and long-term mortality. 7,13,51 A case-control study reported that HbA1c in COPD patients was associated with exacerbation of COPD and was significantly higher compared with those that were stable, which indicated that HbA1c is a good predictor of disease severity in patients with COPD. 7 A cohort study of 526 patients with COPD found that higher HbA1c levels were significantly associated with the risk of severe exacerbation in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported the association of HbA1c level with the exacerbation of COPD, which is a severe complication associated with increased short-and long-term mortality. 7,13,51 A case-control study reported that HbA1c in COPD patients was associated with exacerbation of COPD and was significantly higher compared with those that were stable, which indicated that HbA1c is a good predictor of disease severity in patients with COPD. 7 A cohort study of 526 patients with COPD found that higher HbA1c levels were significantly associated with the risk of severe exacerbation in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…7,13,51 A case-control study reported that HbA1c in COPD patients was associated with exacerbation of COPD and was significantly higher compared with those that were stable, which indicated that HbA1c is a good predictor of disease severity in patients with COPD. 7 A cohort study of 526 patients with COPD found that higher HbA1c levels were significantly associated with the risk of severe exacerbation in patients with COPD. 13 However, an observational study in Greece based on 156 patients with acute exacerbations of COPD (AECOPD) reported that neither the preceding nor the present HbA1c levels exhibit a predictive value regarding short-or long-term outcomes of an AECOPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48 Biologically, unbalanced glucose metabolism may lead to airflow obstruction and reduced lung function by causing endothelial dysfunction, thereby increasing the risk of COPD. 49,50 Furthermore, pathophysiological research has demonstrated that lipid metabolism may be involved in its pathogenesis. 51 For instance, HDL increased the expression of ABCA1 and activated the p38MAPK signaling pathway, which promoted the migration and proliferation of lipopolysaccharide-stimulated alveolar type II epithelial cells, thereby exerting a pro-inflammatory effect.…”
Section: Papermentioning
confidence: 99%